2004
DOI: 10.1111/j.0030-1299.2004.12853.x
|View full text |Cite
|
Sign up to set email alerts
|

Mate limited reproductive success in two dioicous mosses

Abstract: L. 2004. Mate limited reproductie success in two dioicous mosses. Á/ Oikos 104: 291 Á/298.We tested whether mate availability in the pleurocarpous dioicous mosses Rhytidiadelphus triquetrus and Abietinella abietina affects fertilization success by transplanting individual male shoots into non-sporophytic female colonies. Fertilization success in both species was limited by the availability of mates and distance-dependent, and the number of sporophytes produced was higher in R. triquetrus than in A. abietina . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 30 publications
3
51
1
Order By: Relevance
“…With more available habitat, male and female plants could more often grow close enough to each other for fertilization, i.e. within a few decimetres of each other (Bisang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…With more available habitat, male and female plants could more often grow close enough to each other for fertilization, i.e. within a few decimetres of each other (Bisang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, plants of both sexes produce many hundreds of flowers, and an adequate seed bank may be maintained even when seed set is proportionally low. Although there are no comparative studies for woody plants, a study of dioicous mosses found that fertilisation success was also limited in female-biased populations (Bisang et al 2004). overall, gender-dimorphic species had higher levels of pollen limitation than hermaphrodite species in our study, which supports Bond's (1994) extinction risk assessment.…”
Section: Both Populations Of Alseuosmia Quercifoliamentioning
confidence: 99%
“…First, fertilization mainly occurs between individuals in close proximity as a consequence of short dispersal range of the swimming spermatozoids (Bisang et al, 2004). Hence, the sexual partners are principally limited to the shoots growing in the same colony.…”
Section: Introductionmentioning
confidence: 99%